Effect of Weather and Game Factors on Injury Rates in Professional Baseball Players. Issue 4 (March 2022) - Chalmers, Peter N.; Mcelheny, Kathryn; D'Angelo, John; Rowe, Dana; Ma, Kevin; Curriero, Frank C.; Kvit, Anton; Erickson, Brandon J.
Background: Injury rates in baseball players of all ages are increasing. Identifying modifiable risk factors is paramount to implementing injury prevention programs. Purpose/Hypothesis: The purpose was to evaluate the influence of weather (temperature, humidity, atmospheric pressure, and heat index) and game factors (start time, duration, single vs doubleheader) on injury rates in professional baseball players. We hypothesized that colder temperatures would be associated with significantly more injuries per game. Study Design: Case-control study; Level of evidence, 3. Methods: This was a retrospective database study. Two data sets were combined: 1 containing all injuries in Major and Minor League Baseball between 2011 and 2017 and 1 containing all games played in Major and Minor League Baseball during the same period to determine the number of injuries per game. Temperature, humidity, atmospheric pressure, and heat index were determined for each game using the data from the US Environmental Protection Agency. Additional game variables included the level of play, the turf type (natural vs artificial grass), the stadium type (open vs dome vs retractable), the game start time, the game duration, and whether the game was a doubleheader. Then, a multivariate analysis was conducted to determine which factors were associated with the number of injuries per game. Results: In total, our analysis included 33, 587 injuries and 76, 747 games. A total of 25, 776 (33.6%) games contained an injury, and 41% of injuries occurred as multiples per game, with up to 9 injuries per game. The multivariate analysis identified significant associations between game duration and injuries per game ( P < .001; effect size, 0.013) and the level of play and injuries per game ( P < .001; effect size, 0.011). There were significant associations between the venue type ( P < .001), the game start time ( P < .001), humidity ( P < .001), the turf type ( P = .016), and barometric pressure ( P = .031); however, the effect size for each was <0.001, suggesting that these factors are clinically unimportant. Our overall model produced an R 2 of 0.04, indicating that these variables only predicted 4% of the variance in injury risk. Conclusion: In professional baseball, the weather is not associated with injury risk; however, game duration may contribute to injury risk.